Un security council referrals to the international criminal court - Galand, Alexandre Skander (Leiden studies on the frontiers of international law, 2018)
This book offers a unique critical analysis of the legal nature, effects and limits of UN Security Council referrals to the International Criminal Court (ICC). Alexandre Skander Galand provides, for the first time, a full picture of two competing understandings of the nature of the Security Council referrals to the ICC, and their respective normative interplay with legal barriers to the exercise of universal prescriptive and adjudicative jurisdiction. The book shows that the application of the Rome Statute through a Security Council referral is inherently limited by the UN Charter as well as the Rome Statute, and can conflict with other branches of international law, including international human rights law, the law on immunities and the law of treaties. Hence, it spells out a conception of the nature and effects of Security Council referrals that responds to these limits and, in turn, informs the reader on the nature of the ICC itself.